Small cell lung cancer: model of circulating tumor cell tumorospheres in chemoresistance - Lukas Klameth (Nature Portfolio, 2017)
Abstract Small cell lung cancer (SCLC) represents 15% of lung cancers and is characterized by early dissemination, development of chemoresistance and a poor prognosis. A host of diverse drugs failed invariably and its mechanisms of global chemoresistance have not been characterized so far. SCLC represents the prototype of an aggressive and highly metastatic tumor which is ultimately refractory to any treatment. High numbers of circulating tumor cells (CTCs) allowed us to establish 5 CTC cell lines (BHGc7, 10, 16, 26 and UHGc5) from patients with recurrent SCLC. These cell lines exhibit the typical SCLC markers and CTCs of all patients developed spontaneously large multicellular aggregates, termed tumorospheres. Ki67 and carbonic anhydrase 9 (CAIX) staining of tumorosphere sections revealed quiescent and hypoxic cells, respectively. Accordingly, comparison of the chemosensitivity of CTC single cell suspensions with tumorospheres demonstrated increased resistance of the clusters against chemotherapeutics commonly used for treatment of SCLC. Therefore, global chemoresistance of relapsing SCLC seems to rely on formation of large tumorospheres which reveal limited accessibility, lower growth fraction and hypoxic conditions. Since similar tumor spheroids were found in other tumor types, SCLC seems to represent a unique tumor model to study the association of CTCs, metastasis and drug resistance.